The nature and measurement of financial liberalisation : an application to the Caribbean - Greenidge, Kevin ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Attempts to quantify the financial liberalisation efforts for some of the countries in the region.